Layered nano-gratings by electron beam writing to form 3-level diffractive optical elements for 3D phase-offset holographic lithography. Issue 47 (16th November 2015) - Yuan, Liang (Leon); Herman, Peter R.
Abstract : Three-level nano-grating phase masks fabricated by e-beam lithography provided a diamond-like symmetry in holographic exposure and promised 3D complete stopbands. Abstract : A multi-level nanophotonic structure is a major goal in providing advanced optical functionalities as found in photonic crystals and metamaterials. A three-level nano-grating phase mask has been fabricated in an electron-beam resist (ma-N) to meet the requirement of holographic generation of a diamond-like 3D nanostructure in photoresist by a single exposure step. A 2D mask with 600 nm periodicity is presented for generating first order diffracted beams with a preferred π/2 phase shift on the X - and Y -axes and with sufficient 1 st order diffraction efficiency of 3.5% at 800 nm wavelength for creating a 3D periodic nanostructure in SU-8 photoresist. The resulting 3D structure is anticipated to provide an 8% complete photonic band gap (PBG) upon silicon inversion. A thin SiO2 layer was used to isolate the grating layers and multiple spin-coating steps served to planarize the final resist layer. A reversible soft coating (aquaSAVE) was introduced to enable SEM inspection and verification of each insulating grating layer. This e-beam lithographic method is extensible to assembling multiple layers of a nanophotonic structure.